Role of patala kshara and gokshuradi choorna in renal calculi - a clinical study - Rabinarayan Tripathy; Shanu K Babu; P N Rajeshwari; Shaithya Raj; Susmita Priyadarshinee Otta (Wolters Kluwer Medknow Publications, 2021)
Background: Renal calculi or kidney stone disease is a common painful urologic disease causing significant social and financial burden. It has high recurrence rate of nearly fifty (50%) percentage. Ayurveda textual references mention specific diuretic, lithotriptic medicines for Asmari (Renal Calculi) which can provide safe, effective and economical treatment. Aim: To evaluate the combined efficacy of Patala kṣhara (an alkaline powder prepared from ash of Stereospermum chelonoides) and Gokshurdi churna (herbal powder) in the disintegration and expulsion of renal calculus. Materials and Methods: The study was a pre and post clinical trial with 30 patients in a single group selected on the basis of specific inclusion and exclusion criteria (Ultrasonography [USG] evidence of renal calculi up to 8 mm size). They were imparted 500 mg Paṭala kshara capsule with lukewarm water and 6 g Gokshuradi churna with honey internally twice daily after food for a period of 30 days. Assessment were done on 15th, 30th and 60th day for subjective parameters (pain, haematuria, burning micturition and increased frequency of micturition) and on 30th day for objective parameters like size and number of stones and epidermal growth factor receptor. Results: Pain, dysuria, size and number of calculus is statistically significant with P < 0.000. Haematuria showed significance with P < 0.046, burning micturition and increased frequency of micturition were significant with P < 0.008. Conclusion: On analysing the results it can be concluded that Patala kshara and Gokshuradi churna are effective in disintegrating and expelling renal calculus. It is effective in reducing the size and number of stones as well as the clinical symptoms.